Cognitions and practices of parents and teachers on family life, religious observances and civic responsibilities - Cabalag, Adelaida (Animo Repository, 1979)
This study discovered and analyzed the attitudes and practices of parents and teachers of Canossa School, High School Department, towards some aspects of life, namely: a) family life, b) religious observances and c) civic responsibility. The subjects of the study were the 82 parents selected through stratified random sampling and all the 16 high school faculty members employed during the scholastic year 1978-1979. A survey type of study was used to get the necessary data. A questionnaire patterned after that of the Likert Scale was devised after consulting several knowledgeable persons supplemented by some related literature and studies. The conclusions drawn from the findings of the study were: 1) Regarding attitudes on family life, both parents and teachers believed that prayer is vital in family life's stability. 2) Although a positive attitude on religious observances was solicited by both groups, most of the mean scores of the items in the responses of the teachers were higher than those of the parents. While both groups adhered to the principle that honesty is a sign of Christian living, their agree response on the obsoleteness of virtue nowadays seemed to evidence their lack of attention towards this particular Christian value. 3) The total mean score obtained by both groups was on the area on civic responsibility. This however, did not deter them from being aware that they had an important role to play in the community where they belong. 4) Parents and teachers exhibited positive responses regarding their practices on family life. The mean scores of the items on the practices of teachers on family life did not vary from one another. On the other, the result revealed by the mean scores of the practices of parents on family life counterchecked the results revealed by the mean scores of the attitudes of parents on the same area. 5) In practice, most parents and teachers seemed not active in the community they belong, and based on the findings, as a whole, the parents tend to be more civic-minded than the